Current-matching erases the anticipated performance gain of next-generation two-terminal Perovskite-Si tandem solar farms. (1st January 2023) - Patel, M. Tahir; Asadpour, Reza; Bin Jahangir, Jabir; Ryyan Khan, M.; Alam, Muhammad A.
Highlights: Global yield potentials of fixed tilt and tracking solar farms employing bifacial two-terminal tandem are quantified. Effective albedo collection determines the relative performance gain of bifacial 2T tandem systems. Only 3.5–5% gains at optimal albedo conditions are expected worldwide compared to constituent single junction HIT subcell. Deviation of effective albedo from 2T tandem's design albedo erases the gain in yield potential owing to current-matching. Abstract: The bifacial gain of various optimally-tilted, and tracking bifacial farms based on single-junction PERC and HIT technologies are well established. The solar module technology is, however, evolving rapidly with the commercial development of two, three, and four-terminal mono and bifacial HIT-Perovskite tandem cells underway. Given the complexity of current-matching in two-terminal tandem cells and significant variation of the weather conditions across the world, one wonders if the benefits of fixed-tilt and tracking cells obtained for single-junction solar cells would remain for tandem solar cells. In this paper, we use a detailed illumination and temperature-dependent bifacial solar farm model (supported by a detailed physical model for bifacial HIT-Perovskite tandem cells) to show that (a) row-to-row shading in solar arrays significantly suppresses the effective albedo collection and thereby the two-terminal (2T) tandem cell efficiency and relative gain compared to an optimal bifacial HIT cell, (b) the global energy yield potential of fixed-tilted and solar-tracking topologies would improve by adopting a 2T tandem design at optimal albedo, with maximum gain arising for tracking farms, (c) the 2T tandem cell/modules (subcell bandgaps, thickness) must be optimized for maximum benefit, and (d) even a relatively small deviation from the optimum will negate all benefits. Our results will broaden the scope and understanding of the emerging tandem bifacial technology by demonstrating global trends in energy gain for worldwide deployment and the need for location-specific tailoring of the module design.